Kebijakan Pemberantasan Terorisme di ASEAN: Apakah Adil? - Satria Unggul Wicaksana Prakasa; Sholahuddin Al-Fatih; Abdurrahman Raden Aji Haqqi (AL-IHKAM: Jurnal Hukum & Pranata Sosial, 2021)
This research aims to discuss ASEAN counter-terrorism policy and its impact on human rights protection. The terrorism act of Abu Sayyaf in the Philippines, the spread of terrorism in Indonesia by JAT and JAD, and the rebellion movement in Pattani-Thailand are the most heard of terrorism cases in Southeast Asian countries. The research focused on the regulatory through comparative approaches. The result found that ASEAN has an agreement known as ASEAN Convention on Counter-Terrorism (ACCT) for combating terrorism. ACCT implementation in national legal regulations of ASEAN members in the midst of the spread of terrorism plays a crucial role in combating terrorism and its impact on human rights protection. However, the effort of eradicating terrorism in Southeast Asian countries is not in line with the principles of peace and regional integrity. The practice of authoritarianism and militarism has instead become most prominent as a result of perpetuating militarism-based legal regulations in resolving terrorism. Efforts for combating terrorism in Southeast Asia, therefore, leave a serious problem regarding the protection of human rights, the issue of impunity, attacks on civil society, and the involvement of the military which threatens territorial integrity. Those are at cross purposes with ACCT policies as well as national sovereignty, integrity, and security of ASEAN members. (Penelitian ini bertujuan membahas kebijakan anti-terorisme ASEAN dan dampaknya terhadap perlindungan hak asasi manusia. Aksi terorisme Abu Sayyaf di Filipina, penyebaran terorisme di Indonesia oleh JAT dan JAD, serta pemberontakan di Pattani-Thailand adalah kasus-kasus terorisme terpopuler yang terjadi di Asia Tenggara. Penelitian ini fokus pada peraturan perundang-undangan dengan pendekatan komparatif. Hasilnya menunjukkan bahwa ASEAN memiliki kesepakatan yang disebut Konvensi ASEAN tentang Kontra-Terorisme (ACCT) untuk memerangi terorisme. Penerapan ACCT dalam peraturan hukum nasional negara anggota ASEAN di tengah maraknya aksi terorisme sangat penting dalam upaya pemberantasan terorisme dan dampaknya terhadap perlindungan hak asasi manusia di ASEAN. Akan tetapi dalam praktiknya, pemberantasan terorisme di ASEAN masih belum sejalan dengan prinsip perdamaian dan keutuhan kawasan. Praktik otoritarianisme dan militerisme justru menjadi praktik paling menonjol yang dilakukan oleh negara-negara di ASEAN seiring dengan langgengnya regulasi hukum berbasis praktik militerisme dalam menyelesaikan kejahatan terorisme. Pemberantasan terorisme di Asia Tenggara menyisakan masalah serius terkait perlindungan hak asasi manusia, isu impunitas, serangan terhadap masyarakat sipil, dan keterlibatan militer yang mengancam integritas teritorial. Isu-isu tersebut bertentangan dengan Kebijakan ACCT serta kedaulatan, integritas nasional, dan keamanan anggota ASEAN.)